Family business litigation and the political economies of daily life in early modern France - Hardwick, Julie, 1962- (Oxford University Press, 2009)
In 17th-century France, families were essential in the shaping of capitalism and the process of state formation. Exploring civil lawsuits in French cities, 'Family Business' reveals the part that the management of everyday difficulties, in court and out, played in these wider phenomena.